The Effect of Quality of Service on Customer Satisfaction - Abdullah, Akmal; Kasmi, Mauli (Pusat Penerbitan dan Publikasi Ilmiah Fakultas Ekonomi, Universitas Muslim Indonesia, 2021)
This research was conducted with the aim to: (1) Knowing how much influence is generated by the dimension of service quality in this case tangible, realibility, responsiveness, assurance and empathy on customer satisfaction in PT. Bosowa Berlian Motor (Mitsubishi) Makassar: (2) Knowing the most dominant factors affects the dimension of service quality to customer satisfaction. The method carried out in this study is a descriptive analysis that basically wants to test the truth of a hypothesis that collects data on the ground to predict and explain the relationship or influence of one variable on other variables. Many of the samples studied were 100 samples of respondents who were customers at PT. Bosowa Berlian Motor (Mitsubishi). Based on the study concluded that testing doubles the value of F-calculated = 25.443 greater than F-estimated = 2.3113. This shows that variables of physical evidence, reliability, responsiveness, assurance and empathy simultaneously positively affect customer satisfaction in PT. Bosowa Berlian Motor (Mitsubishi) Makassar.